2004
DOI: 10.1002/ijc.20303
|View full text |Cite
|
Sign up to set email alerts
|

KLF6 is not the major target of chromosome 10p losses in glioblastomas

Abstract: Dear Sir,Complete or partial deletions of chromosome 10 are critical events during the malignant progression of gliomas. 1 They are present in the large majority of patients with glioblastoma multiforme (GBM), the most malignant glioma. Recent evidence suggests that complete losses of one copy of chromosome 10 are more frequent in primary GBM and partial losses in secondary GBM. 2 More often deletions affect the long arm of chromosome 10 but in a large fraction of patients they are also present on the short ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…Two of these polymorphims (G3023A and R201R) had been already reported (Kohler et al, 2004;Koivisto et al, 2004a, b;Montanini et al, 2004;Reeves et al, 2004;Boyault et al, 2005). We did not find mutation in KLF6 exon 2 in any of the 76 tumor samples analysed.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Two of these polymorphims (G3023A and R201R) had been already reported (Kohler et al, 2004;Koivisto et al, 2004a, b;Montanini et al, 2004;Reeves et al, 2004;Boyault et al, 2005). We did not find mutation in KLF6 exon 2 in any of the 76 tumor samples analysed.…”
supporting
confidence: 69%
“…Indeed, no mutation was found in a larger series of hepatocellular carcinoma by another group (Boyault et al, 2005). Finally, astrocytic gliomas show the same difference with no mutation found in three different studies (Kohler et al, 2004;Koivisto et al, 2004b;Montanini et al, 2004) after a first report that described 9% of KLF6 mutations in the exon 2 (Jeng and Hsu, 2003).…”
mentioning
confidence: 61%
“…17 However, the extent of KLF6 loss in major human cancers has been recently subjected to passionate debate. Numerous studies now report the absence of somatic mutation nor KLF6 inactivation in colorectal carcinoma, 27 in glioblastomas, 28 in prostate cancer, 29,30 in meningiomas, 28,31 in astrocytic tumors, 32 and, finally, in HCC. 18 Here, we confirmed that KLF6 is not mutated, and expressed in HCC samples, and in HCC-derived cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…So the highly variable frequency of KLF6 mutations may be caused by differences in methodology and sample sets. For example, some reports showed that KLF6 mutations are absent in prostate cancers (Mühlbauer et al, 2003) and human astrocytic gliomas (Koivisto et al, 2004;Köhler et al, 2004;Montanini et al, 2004), while other authors reported high frequencies of KLF6 mutations in prostate cancer (55%) (Narla et al, 2001) and astrocytic gliomas (9%) (Jeng and Hsu, 2003). Therefore, extensive investigation in both HCC and other human cancers is needed to determine the frequency of KLF6 mutation and its role in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%